2021
DOI: 10.2147/ijgm.s333322
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Thyroid-Stimulating Hormone and Long-Term Outcomes in Patients with ST Segment Elevation Myocardial Infarction Treated by Primary Percutaneous Coronary Intervention

Abstract: Objective Thyroid hormones are closely related to the cardiovascular system. Our study aimed to explore the impact of admission thyroid-stimulating hormone (TSH) levels on long-term outcomes in patients with acute ST segment elevation myocardial infarction (STEMI) by detailed stratifications of TSH. Methods Consecutive STEMI patients admitted to our hospital were divided into four groups: Group 1 (TSH <0.35 mIU/L), Group 2 (TSH 0.35–1.0 mIU/L), Group 3 (TSH 1.0–3.5 mIU/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…( 27 ) firstly found that SHyper was associated with an increased risk of cardiac and overall mortality in 1,026 patients with acute cardiac diseases during a 30-month follow-up, whereas only 285 of them were caused by AMI. In contrast, in a recent retrospective study with a median 2.5-year follow-up, no relation was observed between the decreased TSH and poor clinical outcomes in the population of STEMI; however, studied subjects were not further stratified by FT3 or FT4 in this study ( 14 ). The ThyrAMI-1 study also showed that AMI patients in the SHyper group did not alter all-cause mortality relative to those in the euthyroid group ( 28 ).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…( 27 ) firstly found that SHyper was associated with an increased risk of cardiac and overall mortality in 1,026 patients with acute cardiac diseases during a 30-month follow-up, whereas only 285 of them were caused by AMI. In contrast, in a recent retrospective study with a median 2.5-year follow-up, no relation was observed between the decreased TSH and poor clinical outcomes in the population of STEMI; however, studied subjects were not further stratified by FT3 or FT4 in this study ( 14 ). The ThyrAMI-1 study also showed that AMI patients in the SHyper group did not alter all-cause mortality relative to those in the euthyroid group ( 28 ).…”
Section: Discussioncontrasting
confidence: 64%
“…For example, Zhu et al. ( 14 ) reported that increased TSH above the reference range was related to worse long-term prognosis and TSH > 3.5 mIU/L worked as an independent predictor for worse 2.5-year mortality in STEMI patients. Soeiro et al.…”
Section: Discussionmentioning
confidence: 99%
“…31 Moreover, long-term mortality was also significantly higher. [31][32][33] In contrast to these findings, another study found no difference in LV ejection function among individuals with the acute coronary syndrome. 34 In the current study, SCH was associated with a higher risk of acute kidney injury than euthyroid patients.…”
Section: Discussionmentioning
confidence: 80%
“…Low systolic blood pressure is typically accompanied by low diastolic blood pressure, which not only reflects a reduction in cardiac function, but also leads to insufficient coronary perfusion reserve, thereby aggravating myocardial ischemia. [ 40 ] A study by Shiraishi J et al [ 41 ] found that low diastolic blood pressure was linked to higher risk of cardiovascular events and death compared to peripheral diastolic blood pressure of 80–89 mm Hg.…”
Section: Discussionmentioning
confidence: 99%